A Dialog on the First 20 Years of PML Research and the Next 20 Ahead - Pandolfi, Pier Paolo; Bernardi, Rosa (Frontiers in Oncology, 2014)
This introductory article has been written in the form of a conversation between Pier Paolo Pandolfi, Director of the Cancer Center of Beth Israel Deaconess Medical Center in Boston, and Rosa Bernardi, a former post-doctoral fellow in the laboratory of Dr. Pandolfi, now principal investigator at San Raffaele Scientific Institute in Milan, Italy. We have chosen this atypical review format because we want to offer to our readers a more direct and personal perspective on the first 20 years of research over the promyelocytic leukemia gene. This article begins as an interview, but soon transforms into a dialogue where we exchange our thoughts on a number of issues around the past, present and future research over the biology of PML. We were particularly keen on emphasizing the aspects that we find most interesting or challenging, therefore we warn our readers that this will not be a comprehensive essay but rather a very personal view of what has been, is and will be exciting and interesting in the PML world, in our opinion.